THE IMPLEMENTATION OF DEBATE TECHNIQUE TO ACTIVATE STUDENTS’ SPEAKING SKILL - Suryadi Suryadi; Urai Salam; Iwan Supardi (Universitas Tanjungpura, 2018)
AbstractThe method of this research was a descriptive research. The data was collected through the observation checklist from the students’ activity. The result of the implementation of debate technique to activate students’ speaking skill could be seen from the data observation. The result of the data analysis based on the students’ activity in debate technique showed that the process of the students’ activity in applying debate technique could activate the students’ speaking skill. Based on the data of the result the mean score of the students who participated in speaking activities, for all meeting until the last activities could be categorized all students spoke in the class, in each group had a chance to speak and the result were 100%, so the average of the percentage that the researcher got from the activity to the all meetings were 100%, and the result of the aspect speaking skill of the students’ individual score that included accuracy, fluency, appropriacy, and voice mechanic for all students from 28 students in the class were 68,73 qualified as average to good. Keyword: Debate Technique, Activate Students, Speaking Skill